The Nature, Causes, Effects and Mitigation of Climate Change on the Environment (IntechOpen, 2022)
This book examines global warming and climate change over the past five decades in mainly subtropical and tropical countries. The amount and types of changes in these countries vary with the environment but are often less than those occurring in the Arctic and northern countries. Chapters address such topics as the controversy surrounding global warming, the effects of climate change on agriculture, changes in land use and hydrology, and more.